2000
DOI: 10.1046/j.1523-1755.2000.00323.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic effect of parathyroid hormone on NHE3 expression in rat renal proximal tubules

Abstract: Our results indicate that the chronic inhibitory effect of PTH on the renal proximal tubule NHE3 is associated with changes in the expression of NHE3 mRNA levels and protein abundance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 43 publications
3
41
0
3
Order By: Relevance
“…avian kidney; short-circuit current; chloride channels; cystic fibrosis transmembrane regulator; glibenclamide PARATHYROID HORMONE (PTH) is known to affect a number of proximal tubule (PT) transport systems. In rats, rabbits, and other mammalian species, PTH inhibits Na ϩ , fluid, and bicarbonate reabsorption in vivo and in vitro (2,4,16,29; for a review, see Ref. 15).…”
mentioning
confidence: 99%
“…avian kidney; short-circuit current; chloride channels; cystic fibrosis transmembrane regulator; glibenclamide PARATHYROID HORMONE (PTH) is known to affect a number of proximal tubule (PT) transport systems. In rats, rabbits, and other mammalian species, PTH inhibits Na ϩ , fluid, and bicarbonate reabsorption in vivo and in vitro (2,4,16,29; for a review, see Ref. 15).…”
mentioning
confidence: 99%
“…Hypertension  NHE3-mediated Na + /H + due to higher NHE3 phosphorylation on serine 552, redistribution from microvilli to the intermicrovillar region together with its regulatory partner dipeptidyl peptidase IV  NHE3-mediated Na + /H + due to higher NHE3 phosphorylation on serine 552, redistribution of the transporter to the intermicrovillar region (Yang et al, 2008) (Magyar et al, 2000;Panico et al, 2009;Crajoinas et al, 2010) Heart Failure  NHE3-mediated sodium reabsorption due to increased renal cortical NHE3 mRNA and protein levels and lower levels of NHE3 phosphorylation at serine 552 (Lutken et al, 2009;Inoue et al, 2012) tubule NHE3 activity has been consistently reported by several laboratories on both in vivo (Bank and Aynediian, 1976;Girardi et al, 2000) and in vitro studies (Pollock et al, 1986;Mrkic et al, 1992;Mrkic et al, 1993). Experiments performed in vitro and ex vivo provide evidence that the acute inhibition of NHE3 by PTH is mediated by molecular mechanisms the include reduction of the transporter's apparent affinity for protons in consequence of the direct phosphorylation of the exchanger followed by reduction of its maximum velocity due to a decrement of the number of NHE3 molecules expressed at the plasma membrane Collazo et al, 2000).…”
Section: High Salt Dietmentioning
confidence: 85%
“…PTH is primarily involved in modulation of serum calcium and phosphate homeostasis but also acts on the proximal tubule, the thick ascending limb, and the distal convoluted tubule to alter urinary electrolyte and fluid excretion. The inhibitory effect of PTH on renal proximal mRNA and protein abundance Collazo et al, 2000;Zhang et al, 1999;Girardi et al, 2000;Bezerra et al, 2008) Dopamine  NHE3-mediated Na + /H + exchange due to increased endocytosis caused by increased PKA-mediated NHE3 phosphorylation (Gomes & Soares-da-Silva, 2004;Hu et al, 2001;Bacic et al, 2003) Glucagon-like peptide 1  NHE3 activity due to increased NHE3 phosphorylation (Crajoinas et al, 2011;Carraro-Lacroix et al, 2009) Glucagon Acutely - NHE via a PKAdependent pathway Chronically - NHE3 mRNA and protein expression at the plasma membrane (Amemiya et al, 2002) Guanylins  NHE3-mediated Na + /H + due to increased levels of NHE3 PKAdependent phosphorylation and reduction of the exchanger at the plasma membrane (Amorim et al, 2006; Lessa LM, Girardi AC, and Malnic G, unpublished observations)…”
Section: Parathyroid Hormonementioning
confidence: 99%
See 1 more Smart Citation
“…Also, factors that are associated with hypercalcemia increase bicarbonate reabsorption in the PT. As a result of PTH suppression, bicarbonate reabsorption in the PT is enhanced by stimulation of the Na ϩ /H ϩ exchanger (88,89). Volume depletion that is induced by hypercalcemia stimulates angiotensin 2 production and hypokalemia, both of which stimulate bicarbonate reabsorption in the PT (90,91).…”
Section: Kidneymentioning
confidence: 99%